Simulating social interactions for the experimental investigation of joint attention. (March 2017) - Caruana, Nathan; McArthur, Genevieve; Woolgar, Alexandra; Brock, Jon
Highlights: Joint attention should be investigated whilst participants are immersed in a social interaction. Virtual reality paradigms offer the optimal balance between validity and control. Interactions must be believable and realistically complex. Abstract: Social interactions are, by their nature, dynamic and reciprocal − your behaviour affects my behaviour, which affects your behaviour in return. However, until recently, the field of social cognitive neuroscience has been dominated by paradigms in which participants passively observe social stimuli from a detached "third person" perspective. Here we consider the unique conceptual and methodological challenges involved in adopting a "second person" approach whereby social cognitive mechanisms and their neural correlates are investigated within social interactions (Schilbach et al., 2013 ). The key question for researchers is how to distil a complex, intentional interaction between two individuals into a tightly controlled and replicable experimental paradigm. We explore these issues within the context of recent investigations of joint attention − the ability to coordinate a common focus of attention with another person. We review pioneering neurophysiology and eye-tracking studies that have begun to address these issues; offer recommendations for the optimal design and implementation of interactive tasks, and discuss the broader implications of interactive approaches for social cognitive neuroscience.